معاصر تحریکی سیرتی ادب میں اصول ِتدریج کی روایت - Dr. Hafiz Muhammad Hassaan Saeed (الآفاق اسلامی و تحقیقی مجلہ)
In the Twentieth century, after the collapse of a central political institution such as the caliphate, many movements came into existence for the revival of Islam. The leaders and important figures of these movements studied all the topics of Islam, especially Seerah of the Prophet Muhammad (SAW) in such a way that keeping the Seerah of the Prophet Muhammad (SAW), how can an Islamic revolution be established in the modern world? Keeping this goal in mind, the leaders of these movements extracted several principles from the Seerah of the Prophet Muhammad (SAW), one of the most important principle is “Gradualism”. In this article, the above principle in the contemporary Islamic Movements have been examined in detail from an analytical study.